ACHIEVEMENTS IN RHEUMATOLOGY IN THE XXI CENTURY - E. L. Nasonov (Научно-практическая ревматология, 2014)
Immunoinflammatory (autoimmune) diseases are among the most severe chronic diseases in humans. These include autoimmune rheumatic diseases that affect children and adults: rheumatoid arthritis, juvenile arthritides, spondy- loarthritides, psoriatic arthritis, as well as systemic lupus erythematosus and other systemic connective tissue diseases. The article examines the Russian experience of diagnosis and pharmacotherapy of rheumatic diseases and the main trends in research. They include the development of prevention strategy, the introduction of innovative methods for early diagnosis, treatment, and prognosis of outcomes of the most severe forms of autoimmune rheumatic diseases under the concept of personalized medicine.